The effects of a 30 second weight-training program on female collegiate rowers - Lee, M. C.; Belfry, G. R. (Applied Physiology, Nutrition, and Metabolism, 2018)
This study examined the effects of a 30-second weight-training program (30SEC) compared to a low-repetition weight-training program (LoRep) on rowing performance and aerobic endurance for female collegiate rowers (Mean Age 18.6 ± 0.8) over 4 weeks. 30SEC (n=5) performed 5 sets of dumbbell deadlifts (DL) and dumbbell bench pulls (BP) at a range of 18 repetitions in 30 seconds. LoRep (n=5) performed 4-5 sets of 2-6 repetitions of rowing specific exercises. Both regimes performed an identical high volume of aerobic training. 30SEC increased mean weight lifted for both DL (% 103.8%, P = 0.05) and BP(% 63.2%, P = 0.05). 30SEC Improved 2000-m (% -2.4%, P = 0.001) and 1-Minute Rowing performance (% +2.9%, P = 0.05), whereas LoRep did not (% +1.9%, P = 0.05; % +1.2%, P = 0.05, respectively). 10-Stroke Peak Power and 6000 m test times did not change for 30SEC nor LoRep (P = 0.05). VO2max, Peak RAMP Power Output, and RAMP Verification Times did not change for 30SEC nor LoRep (P = 0.05). This study demonstrated that a 30-second weight-training program performed over 4 weeks improves 2000-m rowing performance for female collegiate rowers compared to a low-repetition weight-training program.